MIDIA DIGITAL COMO ALTERNATIVA DE EDUCAÇÃO EM SAÚDE MATERNO INFANTIL - Machado, Camila Aires (2019)
Introduction: In the health area, considering the maternal and child context, educational actions developed through virtual technologies can meet the needs, desires and aspirations of family members / caregivers. Objectives: General: To create a scientific virtual page, through social network, on nursing care, with a multidisciplinary focus on maternal and child themes, as an alternative of health education in digital media. Specific: Develop and include care strategies on the page, which help to expand maternal and child knowledge, based on the needs of the virtual group, enabling reflection and socialization of ideas and care; Evaluate this virtual tool as a health education assistance strategy, from the point of view of users, through access to the virtual page. Methodology: Convergent Care Research (PCA), with a qualitative approach, based on the Freirean problematizing framework. It was developed in an online social network, using Facebook, with the creation of a page in this site, with the name Blog of the Stork. The period of the survey comprised the period from August 2017 to December 2018, and the data collection took place between June and August of 2018. Twenty people from the family nucleus of pregnant women and / or puerperal women participated in the in-box interviews, with doubts regarding issues related to maternity and child development. Results: The data were organized into two categories of analysis in order to achieve the proposed goals: Educational needs and strategies for maternal and child care; Access and evaluation of the virtual page. Thus, the final product of the research has brought important contributions to maternal and child care and attention. The blog was considered by the study participants as an educational tool, collaborating to minimize the main doubts and difficulties presented in daily life. Final considerations: It is concluded that the creation of the scientific virtual page can be a relevant educational care tool, being highly sought after and evaluated positively by adults, with a good level of education and who have doubts and difficulties because they are experiencing the first experience of the maternity and child care. It is evidenced that health professionals should deepen their knowledge regarding the use of information technology, since its use is satisfactory as an educational strategy